Holistic approach in biology and neuroscience, finale debate - VV.AA, VV.AA. (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
LUDOVICO GALLENI: This is very good work done, thank you very much. I think that themain problem of Teilhard at present curiously is that his works are not yet very well known among many people who speak about Teilhard. We had a strong debate in theRome meeting on Darwin in 2009 about this. [...].